Direct and imagined contact moderates the effect of need for cognitive closure on attitudes towards women managers. (6th June 2022) - Baldner, Conrad; Viola, Marta; Capozza, Dora; Vezzali, Loris; Kruglanski, Arie W.; Pierro, Antonio
Abstract: This research investigated the relationship between individual preference for the need for cognitive closure (NCC) and attitudes towards women as managers and the moderating role of direct or imagined contact with women leaders. In two studies (total N  = 369) collected in different countries and with different methods (Study 1: Italy, correlational; Study 2: U.S., experimental), it was found that the positive relationship between NCC and negative attitudes towards women as managers was moderated by the quality, but not the quantity of current or past direct contact experiences with women managers. In Study 1, employees with higher scores on NCC had more positive attitudes towards women managers when they had more positive work experience with women managers. In Study 2, those with higher NCC scores had less negative attitudes towards women as managers when they merely imagined (positive) contact with them (vs. a control group). These results advance the literature on the interaction between NCC and positive intergroup contact; theoretical and practical implications of NCC and positive intergroup contact are presented.